Different patterns of population structure and genetic diversity of three mesopelagic fishes in the Greek Seas - SARROPOULOU, XENIA; TSAPARIS, DIMITRIS; TSAGARAKIS, KONSTANTINOS; BADOUVAS, NICHOLAS; TSIGENOPOULOS, COSTAS S. (Mediterranean Marine Science, 2022)
Mesopelagic fishes are among the most abundant groups of vertebrates on Earth. Despite their unique biological and ecological traits, research in this group has been particularly scarce. The present study investigates the intraspecific genetic diversity of three mesopelagic fishes (Hygophum benoiti, Maurolicus muelleri, and Benthosema glaciale) in the Greek Seas. Analyses of three mitochondrial DNA genes (COI, 12S, and 16S) from a total of 168 samples revealed a lack of genetic structure for M. muelleri and B. glaciale across the studied area. However, H. benoiti specimens from the Corinthian Gulf were differentiated from the rest of the populations, suggesting that the limited connection between the Corinthian and neighboring seas may act as a barrier to gene flow. Furthermore, the COI data of this study were co-analyzed with publicly available sequences, demonstrating lack of phylogeographic structure for all three species through their distribution range. Therefore, even though indications of genetic differentiation were observed, the three mesopelagic fishes are generally characterized by genetic homogeneity, which may be the result of their recent evolutionary history.